Tipping point of plant functional traits of Leymus chinensis to nitrogen addition in a temperate grassland - Yang, Guojiao; Zhang, Zijia; Zhang, Guangming; Liu, Qianguang; Zheng, Peiming; Wang, Renqing (Frontiers in Plant Science, 2022)
It has widely been documented that nitrogen (N) enrichment stimulates plant growth and modifies plant functional traits in the terrestrial ecosystem. However, it remains unclear whether there are critical transitions or tipping points for the response of plant growth or traits to N enrichment, and how these responses differ to different N forms. We chose the native, perennial clonal grass, Leymus chinensis in Inner Mongolia steppe, and conducted a field experiment, in which six N addition rates (0, 2, 5, 10, 20, and 50 g N m–2 year–1) and five N compound types [NH4NO3, (NH4)2SO4, NH4HCO3, CO(NH2)2, slow-release CO(NH2)2] are considered. Here, we found that the different N compound types had no significant effect on the growth of L. chinensis. N addition rate significantly increased plant aboveground biomass and leaf nitrogen concentration, whereas decreased leaf dry matter content. The tipping point for N-induced aboveground biomass increase was at 10 g N m–2 year–1, and the changes in functional traits were at N addition rates of 20 g N m–2 year–1. Our findings suggested that the responses of aboveground biomass and functional traits to N addition were asymmetric, in which responses in aboveground biomass were more sensitive than that in functional traits. The differential sensitivity of aboveground biomass and functional traits of L. chinensis occurred to N deposition highlights the importance of functional traits in mediating ecosystem functioning in the face of N deposition, regardless of which chemical forms dominate in the deposited N.